Mixing Methods in the Age of Migration Politics: A Commentary on Validity and Reflexivity in Current Migration Research. (April 2019) - Horvath, Kenneth; Latcheva, Rossalina
Migration is one of the crucial "wicked problems" of our times, calling for novel research strategies. We point to methodological challenges linked to current migration contexts that are often underappreciated. These challenges follow not so much from the complexity of cross-border mobility itself but rather from the political dynamics that have affected migration practices as well as migration research over the past decades. We identify three basic implications of these developments for mixed methods research in migration contexts: the need (a) to empirically assess nationally framed data infrastructures and research procedures, (b) to justify categories that organize our research and analysis, and (c) to consider the intricate entanglements between (migration) research and (migration) politics.